Participants' Reactions to and Suggestions for Conducting Intimate Partner Violence Research: A Study of Rural Young Adults. Issue 1 (14th July 2015) - Edwards, Katie M.; Greaney, Kayleigh; Palmer, Kelly M.
Abstract: Purpose: To document rural young adults' reasons for emotional reactions to participating in intimate partner violence (IPV) research as well as to hear young adults' perspectives on how to most effectively conduct comprehensive IPV research in their rural communities. Methods: The data presented in this paper draw from 2 studies (ie, an online survey study and an in‐person or telephone interview study) that included the same 16 US rural counties in New England and Appalachia. Participants, 47% of whom were in both studies, were young (age range 18‐24), white (92%‐94%), heterosexual (89%‐90%), female (62%‐68%), and mostly low to middle income. Findings: Nine percent of participants reported they were upset by the questions due to personal experiences with IPV or for other reasons not related to personal IPV experiences. Forty percent of participants reported they personally benefited from participating in the study, and they provided various reasons for this benefit. Regarding suggestions for conducting IPV research with rural young adults, participants believed that both online recruitment and online data collection methods were the best ways to engage young adults, although many participants suggested that more than 1 modality was ideal, which underscores the need for multimethod approaches when conducting research with rural young adults. Conclusions: These findings are reassuring to those committed to conducting research on sensitive topics with rural populations and also shed light on best practices for conducting this type of research from the voices of rural young adults themselves.